THE IMPACT OF GAMIFICATION ON ONLINE LEARNING: ITS EFFECT ON MOTIVATION AND UNDERSTANDING OF STUDENTS - Ulimaz, Almira; Karimah, Saidatul; Cleveresty, Tri Bigrit; Hita, I Putu Agus Dharma (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the impact of gamification in online learning, focusing on its effect on student motivation and understanding. Although online learning is effective in providing flexibility and accessibility, it often faces challenges in maintaining student motivation and engagement. Gamification, which involves applying game elements in an educational context, has been considered a potential solution to enhance student motivation and engagement. Using the literature review method, this research explores various findings from previous studies on the implementation of gamification in higher education. The results indicate that gamification has a positive impact on increasing student motivation and engagement in online learning, especially through elements such as rewards, points, badges, and challenges. However, the effect of gamification on long-term understanding of the material varies. Some studies indicate that while gamification increases short-term motivation, not all game elements contribute significantly to deep understanding. This study suggests integrating gamification with other learning approaches, such as Problem-Based Learning (PBL), to improve long-term student understanding. This research is expected to provide insights for educators and curriculum developers in designing more effective online learning experiences.